2012
DOI: 10.1007/s10911-012-9255-3
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Mammosphere Assay Protocol for the Quantification of Breast Stem Cell Activity

Abstract: Since the discovery that neural tissue contains a population of stem cells that form neurospheres in vitro, sphere-forming assays have been adapted for use with a number of different tissue types for the quantification of stem cell activity and self-renewal. One tissue type widely used for stem cell investigations is mammary tissue, and the mammosphere assay has been used in both normal tissue and cancer. Although it is a relatively simple assay to learn, it can be difficult to master. There are methodological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
313
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 305 publications
(321 citation statements)
references
References 16 publications
5
313
0
3
Order By: Relevance
“…In vivo transplantation is the gold standard assay of CSC‐like properties 18. By the orthotopic injection of breast cancer cells into the mouse mammary gland, we found that the formation of orthotopic tumors in the shFLI‐1 group mice was significantly delayed than that in the shNC group mice (Figure 4D).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In vivo transplantation is the gold standard assay of CSC‐like properties 18. By the orthotopic injection of breast cancer cells into the mouse mammary gland, we found that the formation of orthotopic tumors in the shFLI‐1 group mice was significantly delayed than that in the shNC group mice (Figure 4D).…”
Section: Resultsmentioning
confidence: 95%
“…To further investigate the role of FLI‐1 in breast cancer tumorigenesis in vivo, orthotopic xenografting of tumors was carried out instead of the conventional subcutaneous or tail intravenous injection 19, 20. This method is thought to, at least partially, simulate a biologically relevant microenvironment for tumor cells and is a gold standard to evaluate CSC‐like properties 18, 19. From the histopathological analysis of the harvested orthotopic tumors, we proved that the knockdown of FLI‐1 can decrease the expression of ALDH1 and inhibit tumor growth, which further confirmed the results of the experiments in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Methods issue addresses new and refined approaches as well as some current controversies in the field. In the developmental arena we have included an article comparing leading methods for isolating and separating populations of mammary epithelial cells [1] as well as articles describing protocols for 3D in vitro models [2] and non-adherent sphere assays [3,4] to study morphogenesis/differentiation and stem/progenitor populations, respectively, in vitro. We also include a review by Lewis and Medina in which they continue a critical discussion of the controversies surrounding the use of Matrigel for transplantation methodologies [5].…”
mentioning
confidence: 99%
“…Regarding tumor biology, we have included articles describing methods that should help address the following outstanding problems: what are the molecular and cellular mechanisms that govern progression from confined breast cancer into invasive carcinoma and to metastases [4,7,8]? What drives organ tropism of breast cancer cells during metastasis [9]?…”
mentioning
confidence: 99%